Comparison of Student Learning Activities between the Active Learning Strategy Type Everyone is a Teacher Here and the Type True or False in Class X of Mapat Tunggul Selatan High School - Khoirun Najmi Septiana; Lilis Suryani; Asep Asep (Program Studi Pendidikan Geografi Universitas Pattimura, 2026)
The purpose of this study was to compare student learning activities between the active learning strategy Everyone is a Teacher Here, and True or False type. This type of research is